Exploring the lived experiences of high-performance micro entrepreneurs in Malaysia: a hermeneutic approach - Hassan, Ida Saliny; Salleh, Arfah; Md Saad, Norma; Krauss, S. E.; Mohamed, Mustafa Omar (National Research Council of Thailand, 2015)
Microfinance is often portrayed as the panacea to poverty alleviation and human development. However, the plethora of impact studies in microfinance suggested a varying degree of success amongst countries adopting the Grameen model of microfinance. In the case of Malaysia, impact studies in microfinance have suggested significant improvements on the income and livelihood of the poor. However, only a handful of micro-entrepreneurs have achieved high-performance in their business. Thus, what did these high-performance micro entrepreneurs have done so differently than the rest of their peers? Given the predominance of Muslim micro entrepreneurs in Malaysia, the study also examines whether there is any influence of Islamic faith in their business experience. If so, how did it influence their lived experiences as high-performance micro entrepreneurs? Hence, this study seeks to explore and interpret the lived experiences of these micro entrepreneurs by infusing Heidegger’s interpretive (hermeneutic) phenomenology as part of the study. Using the purposive sampling technique, the informants were selected from Amanah Ikhtiar Malaysia (AIM) for in-depth interviews. Nevertheless, only seven informants are chosen as the saturation point is reached at the seventh informant. Three main themes were inductively derived from the data and evidently, one of the themes suggested that religious values played a significant role in influencing business experience among high-performance micro entrepreneurs. This study hopes to provide a more robust understanding on the entrepreneurship enacted by entrepreneurs living in poverty settings hence serving a practical guidance to policy-makers and development experts in improving current policies.